2011
DOI: 10.1002/ep.10478
|View full text |Cite
|
Sign up to set email alerts
|

A framework development for predicting the longitudinal dispersion coefficient in natural streams using an artificial neural network

Abstract: The main objective of the present investigation is to predict longitudinal dispersion coefficient (K x ) in natural streams using artificial neural network (ANN) technique based on most famous training functions such as Trainlm, Trainrp, Trainscg, Trainoss, and so on. To achieve the goal, hydraulic and geometric data (shear velocity, channel width, local flow depth, and mean longitudinal velocity) that are easily obtained in natural streams are used. First, we have tried to review the most well-known of publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…This procedure must be repeated many times before the network begins to model the relationship. Details for mastering the art of NN model are published elsewhere [28][29][30][31][32][33].…”
Section: Neural Networkmentioning
confidence: 99%
“…This procedure must be repeated many times before the network begins to model the relationship. Details for mastering the art of NN model are published elsewhere [28][29][30][31][32][33].…”
Section: Neural Networkmentioning
confidence: 99%
“…As is presented in Eq.-1, D is needed to be determined before model being run. There are plenty available formulas to determine this coeff icient however not all of them have appropriate performance (Noori 2009;Noori 2011). Due to some newly published studies in the related literature, authors came to the conclusion to choose D that is suggested by Zeng & Huai (2014)in this study (Eq.-2).…”
Section: Methodsand Materialsmentioning
confidence: 99%
“…In order to tackle these issues in intrusive ROMs, a number of non-intrusive reduced order models (NIROMs) have been developed recently [50,53,35,34]. However, very little work can be found addressing non-intrusive model reduction for parameterized PDEs, where inputs (e.g.…”
Section: Introductionmentioning
confidence: 99%